EVALUASI PROGRAM TRANSPORTASI GRATIS UNTUK PELAJAR DI KABUPATEN TUBAN - Kurniawan, Wahyu Bagus; Huda, Muhammad Miftahul; Rupiarsieh (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This research aims to determine the evaluation of the free transportation program for students in Tuban Regency, organized by the Tuban Regency Government through the Environmental and Transportation Agency (DLHP). This research uses a qualitative method that is descriptive in nature. The data collection techniques in this study were conducted through three methods, namely observation, interviews, and document studies. The results of this study indicate that the free transportation program for students in Tuban Regency has not been running optimally. Although the program has provided benefits for students by facilitating free buses and transportation, there are several areas that need improvement, such as the lack of free bus and transportation fleets, the absence of a hotline for public complaints, and the unavailability of an application and tapping system for free transportation, which are only possessed by the "Si Mas Ganteng" bus.